KEMITRAAN STRATEGIS INDONESIA-PERANCIS MELALUI JOINT WORKING GROUP ON TOURISM SEBAGAI UPAYA PENINGKATAN PARIWISATA DI INDONESIA TAHUN 2013-2017 - Fany Samya Rahmadeni; Syafri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to show the problem of tourism in Indonesia. Tourism is one of many sectors which can provide benefits to a country both in economic and cultural aspects. France is one of the countries with the highest tourist visit rates in the world, a possibility to Indonesia to have advantages cooperate with France. This research theoretically has built using the perspective of pluralism in Internasional Relations and supported by International cooperation theory. Formulation of all arguments, data, facts, and theoretical frameworks in this study using the method of qualitative explanation. This research also use nation-states as a level of analysis.This study aims to describe the collaborative efforts of Indonesia and France that have strategic partnership relationship within the frameworks of the joint working group on tourism cooperation can improve tourism in Indonesia. France is a developed country in the field of tourism, for that Indonesia needs to learn from tourism management in France. Furthermore, the biggest foreign tourists coming to Indonesia come from France. Through this Joint Working Group On Tourism, effort to improve tourism in Indonesia can be realized. Keywords : Joint Working Group On Tourism, Tourist, Cooperation, Strategic Partnership